2020
DOI: 10.1177/0734282920943455
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Convergent Validity of the ICAR16 and WAIS-IV

Abstract: The construct validity of the International Cognitive Ability Resource (ICAR) has yet to be investigated using a gold-standard individually administered intelligence battery. The present study used a convenience sample of 97 students to examine the respective relations between the ICAR16 and overall intelligence ( g) and the Cattell–Horn–Carroll broad abilities measured by the WAIS-IV. Large correlations were observed between the observed overall scores (rICAR16, full-scale IQ = .81, p < .001) and the CFA-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Previous research has established that the ICAR 16-item sample test is a reliable and valid measure of global cognitive ability (Condon & Revelle, 2015 ; Merz et al, 2020 ). The (self-administered) ICAR-16 shows high convergent validity with the Wechsler Adult Intelligence Scale (fourth edition) administered by a trained clinician ( r = 0.81 and r = 0.94 with the manifest and the latent score of the WAIS-IV, respectively, Young & Keith, 2020 ). As pedohebephilic participants might have a stronger motivation than teleiophilic MTurkers to excel on the IQ test, it was planned to compare their responses with scores obtained among Internet users who wanted to test their cognitive abilities in a previous study (Condon & Revelle, 2015 ).…”
Section: Methodsmentioning
confidence: 98%
“…Previous research has established that the ICAR 16-item sample test is a reliable and valid measure of global cognitive ability (Condon & Revelle, 2015 ; Merz et al, 2020 ). The (self-administered) ICAR-16 shows high convergent validity with the Wechsler Adult Intelligence Scale (fourth edition) administered by a trained clinician ( r = 0.81 and r = 0.94 with the manifest and the latent score of the WAIS-IV, respectively, Young & Keith, 2020 ). As pedohebephilic participants might have a stronger motivation than teleiophilic MTurkers to excel on the IQ test, it was planned to compare their responses with scores obtained among Internet users who wanted to test their cognitive abilities in a previous study (Condon & Revelle, 2015 ).…”
Section: Methodsmentioning
confidence: 98%
“…This is an open-access test of general cognitive ability, which requires participants to complete 16 items across four item types: matrix reasoning, verbal reasoning, three-dimensional rotation, and letter-number sequences. In the original validation study, the ICAR sample test had good internal consistency (alpha = .81), and good convergent validity (correlating at approximately .8 with commercial IQ measures when correcting for reliability and restriction of range; Condon & Revelle, 2014 ; Young & Keith, 2020 ).…”
Section: Methodsmentioning
confidence: 98%
“…The developers aimed to create items that could not be easily referenced elsewhere to reduce the likelihood of cheating. An independent factor analytic study found the ICAR measures fluid reasoning and visual-spatial broad abilities consistent with the Cattell-Horn-Carroll theory (Young & Keith, 2020), though the ICAR was not explicitly developed based on this framework.…”
Section: Methodsmentioning
confidence: 98%
“…Data were collected as part of a convergent validity study of the ICAR and Wechsler Adult Intelligence Scale, Fourth Edition (WAIS-IV; Young & Keith, 2020). The sample consisted of 97 university students from a large, southwestern university.…”
Section: Methodsmentioning
confidence: 99%